Study on the Capacity Assessment and Optimization Path of Social Organizations in Assisting Rural Revitalization - 玉璞李; Wang, Yu (Pacific International Journal, 2023)
Participation in rural revitalization is a crucial responsibility for social organizations. It not only demonstrates their commitment to serving the country, society, the public, and the industry but is also a vital avenue for achieving high-quality development. To assess the ability of social organizations to contribute to rural revitalization, we constructed an evaluation index system. We employed the TOPSIS evaluation and barrier degree model to evaluate the ability of Chinese social organizations, private non-enterprises, and foundations to participate in rural revitalization in our research area. Our results indicate that the overall ability of social organizations to participate in rural revitalization is at a medium-low level, and three major obstacles exist in the areas of organizational construction, basic guarantee, and project participation. Therefore, we should focus on improving the organizational construction capacity by strengthening the "internal strength of the organization" and cultivate the basic guarantee capacity by paying attention to "own finance." We should also enhance the participation capacity of rural revitalization projects by setting "participation targets" and relying on the "internal strength of the organization." We propose optimization paths from various perspectives, including practicing "internal strength of the organization" and actively improving the capacity of organization construction, paying attention to "own finance" and continuously cultivating the capacity of basic guarantee, focusing on "participation targets" and effectively strengthening the capacity of participation in rural revitalization projects, relying on "digital empowerment" and enhancing the professional service capacity of social organizations, integrating "rural demands" and improving the policy coordination capacity of social organizations.